The document discusses addition and multiplication of matrices. It provides examples of adding two matrices of the same order, as well as multiplying a matrix by a scalar value. Key points include:
- To add matrices, corresponding elements are added if the matrices are the same order
- Multiplying a matrix by a scalar involves multiplying each element of the matrix by the scalar value
- Examples are provided to demonstrate calculating the sum and product of matrices step-by-step
1 of 61
More Related Content
V2.0
1. Addition of Matrices
Individual elements are added
Both matrices must be of the same order
If A =
?11 ?12 ?13
?21 ?22 ?23
is a 2 〜 3 matrix
and B =
?11 ?12 ?13
?21 ?22 ?23
is another 2 〜 3 matrix.
Then, A + B =
?11 + ?11 ?12 + ?12 ?13 + ?13
?21 + ?21 ?22 + ?22 ?23 + ?23
i.g. : If A =
1 2 ?4
2 3 7
and B =
4 ?1 1
3 1 0
Then, A + B =
1 + 4 ?1 + 2 ?4 + 1
2 + 3 3 + 1 7 + 0
A + B =
5 1 ?3
5 4 7
2. Example 6
Given A = 3 1 ?1
2 3 0
and B =
2 5 1
?2 3
1
2
, find A + B
A + B = 3 1 ?1
2 3 0
+
2 5 1
?2 3
1
2
=
3 + 2 1 + 5 ?1 + 1
2 ? 2 3 + 3 0 +
1
2
=
2 + 3 1 + 5 0
0 6
1
2
3. Multiplication of Matrice by a scalar
If A = [aij] m 〜 n is a matrix and k is a scalar,
then kA = k [aij]m 〜 n = [k (aij)] m 〜 n, that is, (i, j)th element of
kA
is kaij for all possible values of i and j.
Every element is multiplied by the scalar.
Eg: If A =
3 1 1.5
5 7 ?3
2 0 5
, then
3A = 3
3 1 1.5
5 7 ?3
2 0 5
3A =
3 〜 3 3 〜 1 3 〜 1.5
3 〜 5 3 〜 7 3 〜 ?3
3 〜 2 3 〜 0 3 〜 5
=
9 3 4.5
3 5 21 ?9
6 0 15
4. Multiplication of Matrice by a scalar
Negative of a matrix
Denoted by CA.
We define CA = (-1) A
Eg: A =
3 1
?5 ?
,
then -A = (-1) A = (-1)
3 1
?5 ?
=
?3 ?1
5 ??
7. Ex 3.2,1
Let A =
2 4
3 2
, B =
1 3
?2 5
, C =
?2 5
3 4
Find each of the following
(i) A + B
A + B =
2 4
3 2
+
1 3
?2 5
=
2 + 1 4 + 3
3 ? 2 2 + 5
=
3 7
1 7
8. Ex 3.2,1
Let A =
2 4
3 2
, B =
1 3
?2 5
, C =
?2 5
3 4
Find each of the following
(ii) A C B
A C B =
2 4
3 2
?
1 3
?2 5
=
2 ? 1 4 ? 3
3 ? (?2) 2 ? 5
=
1 1
3 + 2 ?3
=
1 1
5 ?3
9. Ex3.2,1
Let A =
2 4
3 2
, B =
1 3
?2 5
, C =
?2 5
3 4
Find each of the following
(iii)3A C C
Finding 3A
3A = 3
2 4
3 2
=
3 〜 2 3 〜 4
3 〜 3 3 〜 2
=
6 12
9 6
Hence
3A C C =
6 12
9 6
?
?2 5
3 4
=
6 ? (?2) 12 ? 5
9 ? 3 6 ? 4
13. Ex3.2, 2
Compute the following:
(i)
a b
?b a
+
a b
b a
a b
?b a
+
a b
b a
=
a + a b + b
b + b a + a
=
2a 2b
0 2a
14. Ex3.2,2
Compute the following:
(ii)
a2 + b2 b2 + c2
a2 + c2 a2 + b2
+
2ab 2bc
?2ac ?2ab
a2 + b2 b2 + c2
a2 + c2 a2 + b2
+
2ab 2bc
?2ac ?2ab
=
a2 + b2 + 2ab b2 + c2 + 2bc
a2 + c2 ? 2ac a2 + b2 ? 2ab
=
a + b 2 b + c 2
a ? c 2 a ? b 2
Using ( a + b)2 = a2 + b2 + 2ab)
& (a C b)2 = a2 + b2 C 2ab
15. Ex3.2, 2
Compute the following:
(iv)
cos2 x sin2 x
sin2 x cos2 x
+
sin2 x cos2 x
cos2 x sine2 x
cos2 x sin2 x
sin2 x cos2 x
+
sin2 x cos2 x
cos2 x sin2 x
=
cos2 x + sin2 x sin2 x + cos2 x
sin2 x + cos2 x cos2 x + sin2 x
=
1 1
1 1
( sin2 x + cos2 x = 1)
19. Ex3.2, 11
If x
2
3
+ y
?1
1
=
10
5
, find values of x and y.
x
2
3
+ y
?1
1
=
10
5
2?
3?
+
??
? =
10
5
2? ? ?
3? ? ?
=
10
5
Since the matrices are equal.
corresponding elements are equal
2x ? y = 10
3x + y = 5
´(1)
´(2)
20. Adding (1) & (2)
(2x C y) + (3x + y) = 10 + 5
2x C y + 3x + y = 15
2x + 3y C y + y = 15
5x + 0 = 15
x =
15
5
x = 3
Putting value of x in (1)
2x C y = 10
2(3) C y = 10
6 C y = 10
C y = 10 C 6
C y = 4
y = C 4
Hence, x = 3 & y = C 3
21. Ex3.2, 4
If A =
1 2 ?3
5 0 2
1 ?1 1
, B =
3 ?1 2
4 0 5
2 0 3
and , C =
4 1 2
0 3 2
1 ?2 3
then compute (A+B) and (B C C) . Also, verify that
A+(B - C) = (A+B) C C
Calculating A + B
A + B =
1 2 ?3
5 0 2
1 ?1 1
+
3 ?1 2
4 0 5
2 0 3
=
1 + 3 2 ? 1 ?3 + 2
5 + 4 0 + 2 2 + 5
1 + 2 1 + 0 1 + 3
=
4 1 ?1
9 2 7
3 ?1 4
22. Calculating B C C
B C C =
3 ?1 2
4 2 5
2 0 3
C
4 1 2
0 3 2
1 ?2 3
=
3 ? 4 2 ? 1 ?3 + 2
4 ? 0 0 + 2 2 + 5
2 ? 1 0 ? (?2) 3 ? 3
=
?1 ?2 0
4 ?1 3
1 2 0
We need to verify
A + (B C C) = (A + B) C C
Taking L.H.S
A + (B C C) =
1 2 ?3
5 0 2
1 ?1 1
+
?1 ?2 0
4 ?1 3
1 2 0
25. Ex3.2, 6
Simplify cos θ
cos θ sin θ
?sin θ cos θ
+ sin θ
sin θ ?cos θ
cos θ sin θ
cos θ
cos θ sin θ
?sin θ cos θ
+ sin θ
sin θ ?cos θ
cos θ sin θ
=
cos θ(cos θ) cos θ(sin θ)
cos θ (????θ) cos θ(cos θ)
+
sin θ(sin θ) sin θ(?cos θ)
sin θ(cos θ) sin θ(sin θ)
=
cos2 θ cos θ sin θ
?cos θ sin θ cos2 θ
+
sin2 θ ?cos θ sin θ
sin θ cos θ sin2 θ
=
cos2 θ + sin2 θ sin θ cos θ ? cos θ sin θ
?cos θ sin θ + sin θ cos θ cos2 θ sin2 θ
=
1 0
0 1
(× cos2θ + sin2θ = 1)
26. Ex3.2, 22
Assume X, Y, Z, W and P are matrices of order 2 〜 n, 3 〜 k, 2 〜
p, n 〜 3 , and p 〜 k respectively.
If n = p, then the order of the matrix 7X C 5Z is
(A)p 〜 2 (B) 2 〜 n (C) n 〜 3 (D) p 〜 n
7X C 5Z
= 7 X 2 〜 ? - 5 Z 2 〜?
This is possible only when
Order of X = Order of Z
2 〜 n = 2 〜 p
Therefore, n = p
So, the matrix 7X C 5Z = 7 X 2 〜 ? - 5 Z 2 〜 ?
Hence, the order of matrix 7X ? 5Z is 2 〜 n.
Hence, correct answer is B
Given order of X is 2 〜 n
and order of Z is 2 〜 p
27. Example 9,
Find X and Y , if X + Y =
5 2
0 9
and X C Y =
3 6
0 ?1
It is given that
X + Y =
5 2
0 9
X C Y =
3 6
0 ?1
`Adding (1) and (2)
(X + Y) + (X C Y) =
5 2
0 9
+
3 6
0 ?1
X + X + Y C Y =
5 + 3 2 + 6
0 + 0 9 ? ( ?1)
´ (1)
´ (2)
28. X + X + Y C Y =
5 + 3 2 + 6
0 + 0 9 ? ( ?1)
2X =
8 8
0 8
X =
1
2
8 8
0 8
X =
8
2
8
2
0
8
2
X =
4 4
0 4
29. Putting X =
4 4
0 4
in (1)
X + Y =
5 2
0 9
Y =
5 2
0 9
C X
Y =
5 2
0 9
-
4 4
0 4
Y =
5 ? 4 2 ? 4
0 ? 0 9 ? 4
Y =
1 ?2
0 5
Hence, X =
4 4
0 4
, Y =
1 ?2
0 5
30. Ex3.2, 7
Find X and Y, if
(i) X + Y =
7 0
2 5
and X C Y =
3 0
0 3
Let X + Y =
7 0
2 5
X C Y =
3 0
0 3
Adding (1) and (2)
X + Y + X C Y =
7 0
2 5
+
3 0
0 3
X + Y + X C Y =
7 + 3 0 + 0
2 + 0 5 + 3
2x + 0 =
10 0
2 8
´(1)
´(2)
32. Putting value of X in (1)
X + Y =
7 0
2 5
Y =
7 0
2 5
C X
Y =
7 0
2 5
C
5 0
1 4
Y =
7 ? 5 0 ? 0
2 ? 1 5 ? 4
Y =
2 0
1 1
Hence X =
5 0
1 4
& Y =
2 0
1 1
44. Ex3.2,9
Find x and y, if 2
1 3
0 ?
+
? 0
1 2
=
5 6
1 8
Given that
2
1 3
0 ?
+
? 0
1 2
=
5 6
1 8
1 〜 2 3 〜 2
0 〜 2 ? 〜 2
+
? 0
1 2
=
5 6
1 8
2 6
0 2?
+
? 0
1 2
=
5 6
1 8
2 + ? 6 + 0
0 + 1 2? + 2
=
5 6
1 8
Since matrices are equal.
Corresponding elements are equal
45. Since matrices are equal, corresponding elements are equal
Therefore,
2 + y = 5
2x + 2 = 8
Solving (1)
2 + y = 5
y = 5 C 2
y = 3
Solving (2)
2x + 2 = 8
2x = 8 C 2
2x = 6
x =
6
2
x = 3
´(1)
´(2)
48. Since matrices are equal, corresponding elements are equal
2x + 3 = 9
2y = 12
2z C 3 = 15
2t + 6 = 18
Solving equation (1)
2x + 3 = 9
2x = 9 C 3
x =
6
2
x = 3
´(1)
´(2)
´(3)
´(4)
49. Solving equation (2)
2y = 12
y =
12
2
y = 6
Solving equation (3)
2z C 3 = 15
2z = 15 + 3
2z = 18
z =
18
2
x = 9
50. Solving equation (4)
2t + 6 = 18
2t = 18 C 6
2t = 12
t =
12
2
t = 6
Hence x = 3 , y = 6 , z = 9 & t = 6
51. Ex3.2,12
Given 3
x z
z w
=
x 6
?1 2w
+
4 x + y
z + w 3
find the values
of x, y, z and w.
3
x z
z w
=
x 6
?1 2w
+
4 x + y
z + w 3
x 〜 3 z 〜 3
z 〜 3 w 〜 3
=
x + 4 6 + x + y
?1 + z + w 2w + 3
3x 3z
3z 3w
=
x + 4 6 + x + y
1 ? z + w 2w + 3
Since matrices are equal.
Corresponding elements are equal
52. Since matrices are equal, corresponding elements are equal
3x = x + 4
3y = 6 + x + y
3z = 1 C z + w
3w = 2w + 3
Solving equation (1)
3x = x + 4
3x C x = 4
2x = 4
x =
4
2
x = 2
´(1)
´(2)
´(3)
´(4)
53. Solving equation (2)
3y = 6 + x + y
3y C y = 6 + x
2y = 6 + x
Putting x = 2
2y = 6 + 2
2y = 8
2y =
8
2
y = 4
54. Solving equation (4)
3w = 2w + 3
3w C 2w = 3
w = 3
Solving equation (3)
3z = C 1 + z + w
3z C z = C 1 + w
2z = C 1 + w
Putting w = 3
2z = C 1 + 3
2z = 2
z =
2
2
z = 1
Hence, x = 2, y = 4 , w = 3 & z = 1
55. Ex3.2,13
If F (x) =
cos ? ?sin ? 0
sin ? cos ? 0
0 0 1
, Show that F(x) F(y) = F(x + y)
F (x) =
cos ? ?sin ? 0
sin ? cos ? 0
0 0 1
We need to show
F(x) F(y) = F(x + y)
Taking L.H.S.
Finding F(x)
F (x) =
cos ? ?sin ? 0
sin ? cos ? 0
0 0 1
56. Finding F(y)
Replacing x by y in F(x)
F (y) =
cos ? ?sin ? 0
sin ? cos ? 0
0 0 1
Now,
F(x) F(y)
=
cos ? ?sin ? 0
sin ? cos ? 0
0 0 1
cos ? ?sin ? 0
sin ? cos ? 0
0 0 1
=
cos ? cos ? + ?sin ? sin ? + 0 cos ?(? sin ?) + (? sin ?) cos + 0 0 + 0 + 0 〜 1
?sin ? cos ? + cos ? sin ? + 0 sin ? (? sin ?) + cos ? cos ? + 0 0 + 0 + 0 〜 1
0 〜 cos ? + 0 + sin ? + 0 〜 1 0 〜 (? sin ?) + 0 〜 cos ? + 0 0 + 0 + 1 〜 1
=
cos ? cos ? ?sin ? . sin ? ?cos ? ? sin ? ? sin ? cos ? 0
sin ? cos ? + cos ? sin ? ? sin ? ? sin ? + cos ? cos ? 0
0 0 1
57. =
cos ? cos ? ?sin ? . sin ? ?cos ? ? sin ? ? sin ? cos ? 0
sin ? cos ? + cos ? sin ? ? sin ? ? sin ? + cos ? cos ? 0
0 0 1
We know that cos x cos y C sin x sin y = cos (x + y)
& sin x cos y + cos x sin y = sin (x + y)
=
cos(? + ?) ?[cos ? sin ? + sin ? cos ?] 0
sin(? + ?) cos ? cos ? ? sin ? sin ? 0
0 0 1
=
cos(? + ?) ? sin(? + ?) 0
sin(? + ?) cos(? + ?) 0
0 0 1